PENGEMBANGAN MODUL MATEMATIKA 3 DENGAN MODEL NHT UNTUK MENINGKATKAN PRESTASI BELAJAR MAHASISWA PGSD UNIVERSITAS PGRI YOGYAKARTA - Danuri Danuri (Universitas Muhammadiyah Surakarta, 2018)
Abstract: This research aims to produce learning media in the form of mathematics module 3 with cooperative learning type numbered head together (NHT) to improve student learning achievement of PGSD in response aspect. students towards developed Modules. This research is a Research and Development (RD) which using ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model with Math Module 3 product using cooperative learning type numbered head together (NHT). The development process was done by several stages of analysis, design, development, implementation, and evaluation. The development model used is a procedural development model, which is a descriptive model, outline the steps to be followed to produce the product. The results showed the quality of Mathematics Module 3 with cooperative learning type numbered head together (NHT) in good category with the percentage of idealization of 73.06% with the detail of content feasibility component in both category with the percentage of 71,39% of the idealization, the linguistic component in good category with the percentage of 74.55% of the idealization, and so are the components of the presentation in either category with an ideal percentage of 74.76%. Response to this module belongs to the category of positive responses with a score of 63.69 from the ideal maximum score of 80. Based on the post-test value, Mathematics 3 module with cooperative learning type numbered head together (NHT) has been successful in improving learning achievement by post-test score of 77.09.